Prevalence of Potentially Pathogenic Bacteria in Rodent Populations Near Natural Water Bodies From Sarawak - Muhammad Amin Iman, Azmi (Universiti Malaysia Sarawak, 2024)
The gut microbiota of rodents forms a dynamic ecosystem within the gastrointestinal tract, actively contributing to the host’s physiological processes. The gut microbiome composition of wild rodents in particular could be influenced by external environmental factors. However, the specific determinants within the environments that directly affect the gut environment of wild rodents remain uncertain. One such influential factor could be natural water bodies, where bacterial communities can exploit the readily available organic matter for growth and circulate with the surrounding rodent populations. Additionally, rodents are known to be natural reservoirs of pathogenic bacteria due to their synanthropic nature and can transmit them through various pathways. Hence, this study aims to characterise the gut microbiome of wild rodents near natural water bodies and to identify pathogenic bacteria within the gut environment. To achieve these objectives, sampling was conducted across forested areas throughout Sarawak. Faecal samples of wild rodents were collected from a total of five sampling sites located near human settlements, accompanied by water quality sampling of natural water bodies across these localities. Nanopore sequencing was performed on the extracted faecal DNA for the characterisation of the gut microbiome of 16 wild rodent individuals belonging to six different species. A total of 1052 bacterial genera were detected, contributing to the gut microbiota of rodents at varying compositions and abundances. The most prominent bacterial families include Lachnospiracea, Lactobacillaceae and Oscillospiraceae, belonging to the phylum Bacillota. They could be considered members of the core rodent gut microbiome due to their high prevalence across various rodent individuals. Also, potentially pathogenic bacteria were detected, and they represent 11% of the total overall abundance. 51 potentially pathogenic bacterial genera, comprising of 774 species, that can cause zoonotic diseases were detected from all sampling iv sites, notably from the genera Clostridium, Klebsiella and Helicobacter. Additionally, while water quality parameters did not exhibit a significant association with the alpha diversity of the gut microbiome or the abundance of pathogenic bacteria, the genus Enterococcus displayed a positive correlation with biochemical oxygen demand. Overall, the characterisation of the gut microbiome of wild rodents across different localities revealed distinct variations. The site-specific bacterial species detected in this study highlights the potential environmental influences on the gut microbiota. This includes the detection of pathogenic bacteria that could potentially transmit to nearby human settlements, implying considerable health concerns.